Ultrasound accuracy in prenatal diagnosis of abnormal placentation of posterior placenta previa. (November 2019) - Garofalo, Anna; Pilloni, Eleonora; Alemanno, Maria Grazia; Garofalo, Giulia; Sciarrone, Andrea; Todros, Tullia; Viora, Elsa
Abstract: Objectives: To evaluate the accuracy of ultrasound in prenatal diagnosis of Placenta accrete spectrum disorders in patients with posterior placenta previa, and to assess the impact of prenatal diagnosis in our population. Study Design: We prospectively enrolled 198 women with posterior placenta previa from 2011 to 2017. We performed transabdominal and transvaginal ultrasound examinations (Grey-scale and colour/power Doppler). The diagnosis of placenta accreta spectrum disorders was based on detection of at least two of the following criteria: loss of retroplacental clear zone, interruption of uterine serosa–bladder wall interface, turbulent placental lacunae with high velocity flow, myometrial thickness <1 mm, increased vascularity of uterine serosa–bladder wall interface, loss of vascular arch parallel to basal plate and/or irregular intraplacental vascularization. Definitive diagnosis was made at delivery with Caesarean section. Furthermore, we compared maternal outcomes in cases diagnosed antenatal versus that one's diagnosed at delivery. Results: There were 20/198 cases of placenta accreta spectrum disorders. The two-criteria system identified 12 cases of placenta accreta, providing a 60.0% of sensitivity, 98.8% of specificity, 85.7% of positive and 95.7% of negative predictive value. Maternal outcomes were better in women with prenatal diagnosis of placenta accreta spectrum disorders, although not statistical significant. Conclusions: Our data showed that grey-scale and Color-Doppler ultrasound evaluation for detecting placenta accreta spectrum disorders on posterior placenta previa have high specificity, positive and negative predictive value, but a low sensitivity. Nevertheless, an antenatal diagnosis of placenta accreta spectrum disorders for posterior placenta previa should be encouraged.